2023
DOI: 10.1002/bio.4445
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of afterglow and photochromic fibrous mats from polypropylene plastics to detect ultraviolet light

Abstract: Polypropylene textiles have been used in the development of various industrial products, such as automotives, plastic furniture, and medical tools. However, polypropylene resists dyeing due to a deficiency of active staining spots. Here, we developed a new strategy towards new afterglow and photochromic fibres from recycled polypropylene plastics using plasma‐supported coloration with rare‐earth activated aluminate nanoparticles (REANPs). Plasma curing was used to generate active dyeing sites on the polypropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The obtained results showed that ceria‐doped zinc oxide had good photoactivity related to nano zinc oxide particles for methylene blue dye deterioration by passing UV light. El‐Hefnawy et al [57] developed polypropylene plastic‐based afterglow and photochromic fibrous mats, demonstrating excellent colour resistance, antimicrobial action, and UV light‐blocking capacity. Finally, Fredrick et al [58] developed DNA‐templated silver nanoclusters (AgNC@DNA) to determine cancer‐associated miRNA via a fluorescence switching method.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…The obtained results showed that ceria‐doped zinc oxide had good photoactivity related to nano zinc oxide particles for methylene blue dye deterioration by passing UV light. El‐Hefnawy et al [57] developed polypropylene plastic‐based afterglow and photochromic fibrous mats, demonstrating excellent colour resistance, antimicrobial action, and UV light‐blocking capacity. Finally, Fredrick et al [58] developed DNA‐templated silver nanoclusters (AgNC@DNA) to determine cancer‐associated miRNA via a fluorescence switching method.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…[23] The luminescent emission in PMMA samples co-doped by trivalent rare earth elements was also reported. [24,25] The main elaboration methods to embed the doping elements within the PMMA matrix consist of adding the dopants to the monomer mixture during the pre-polymerization step, [26] the direct mechanical mixing of the dopants with the melted PMMA during the extrusion process [27] or in soaking the dopant molecules into the microstructure fiber using the solution-doping method. [28] In our work, we present a new class of transparent PMMA fibers doped with transition metal oxide-based photochromic materials, namely tungsten oxide compounds (WO 3 ), for X-chromic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, polypropylene has been the second-largest general-purpose plastic used in China [1] . The price is low, and it has the advantages of being odorless and having low heat processing temperature, so it is widely used daily.…”
Section: Introductionmentioning
confidence: 99%